The next generation of therapy for multiple myeloma: a review of ongoing clinical trials utilizing ClinicalTrials.gov. (18th July 2018) - Barth, Peter; Vale, Colin; Chambers, Alison B; Reagan, John L
The therapeutic armamentarium for multiple myeloma has grown significantly over the past decade. We characterized ongoing multiple myeloma clinical trials utilizingClinicalTrials.gov . A search ofClinicalTrials.gov on 21 April 2017 returned 239 therapeutic interventional trials in multiple myeloma. A majority (84.1%) of trials are early-phase (I/II). Immunotherapies are significantly more likely to be studied in Phase I trials than Phase II trials (p = 0.0049). Primary sponsor (academic, cooperative group, industry) is significantly associated with phase of trial (p = 0.0334). Quality of life assessment is included as a secondary objective in only 10.1% of trials. Areas of need are continued advancement of immunotherapies, late-phase studies utilizing a triplet control group, and an objective focus on quality of life.